1st place, PREMUS best paper competition: workplace and individual factors in wrist tendinosis among blue-collar workers − the San Francisco study - Carisa Harris; Ellen A Eisen; Robert Goldberg; Niklas Krause; David Rempel (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: Workplace studies have linked hand/wrist tendinosis to forceful and repetitive hand exertions, but the associations are not consistent. We report findings from a prospective study of right wrist tendinosis among blue-collar workers. METHODS: Workers (N=413) at four industries were followed for 28 months with questionnaires and physical examinations every 4 months to identify incident cases of right wrist tendinosis. Exposure assessment of force and repetition were based on field measurements and video analysis to determine repetition rate and the percent time (% time) in heavy pinch (>1 kg-force) or power grip (>4 kg-force). All exposure variables were measured at the level of the individual and task. For workers responsible for >1 task, a time-weighted average exposure was calculated based on task hours per week. A proportional hazards model was used to assess the relationship between exposures and incidence of wrist tendinosis. RESULTS: During the 481 person-years of follow-up, there were 26 incident cases of right wrist tendinosis [incidence rate (IR) 5.40 cases per 100 person-years]. Adjusting for age, gender, and repetition, wrist tendinosis was associated with % time spent in heavy pinch [hazard ratio (HR) 5.01, 95% CI 1.27-19.79). Composite exposure measure American Conference of Industrial Hygienists Threshold Limit Value (ACGIH-TLV) for hand activity level (HR 3.95, 95% CI 1.52-10.26) was also associated with the outcome for the medium-exposure group using video-based total repetition rate. CONCLUSIONS: The workplace factors predicting wrist tendinosis were time-weighted average values of % time spent in heavy pinch and the ACGIH-TLV for Hand Activity Level. The % time spent in power grip was not a significant predictor, nor were any measures of repetition. An exposure−response relationship was observed for the % time spent in heavy pinch. These findings may improve programs for preventing occupational wrist tendinosis.